2001
DOI: 10.3109/15622970109026807
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of β-Hexosaminidase (uHex) and γ-Glutamyl-Transferase (uGGT) in Urine as Non-Invasive Markers of Chronic Alcohol Abuse: I. Alcohol-Dependent Subjects

Abstract: It has been demonstrated that in alcohol-dependent men the uHex test is one of the most powerful discriminating tools, while uGGT has a discriminating power similar to that of sHex but worse than that of uHex, sGGT and s%CDT. Receiver Operating Characteristic (ROC) areas under the curves (AUC) for uHex, uGGT, s%CDT, sHex and sGGT were 0.92, 0.79, 0.88, 0.79 and 0.92, respectively. Due to their good parameters, low cost, ease of use and non-invasive character the uHex and uGGT tests are useful tools for the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The present study confirmed the results of our preliminary work on uHex utility in alcohol-dependent men (21,22), and showed negligible bias from endogenous inhibitors of the enzyme. This finding and the slightly, albeit non-significantly, higher AUC value ( Table 2) mean that uHex is superior to eAAP as a possible clinical marker.…”
Section: Markersupporting
confidence: 94%
See 3 more Smart Citations
“…The present study confirmed the results of our preliminary work on uHex utility in alcohol-dependent men (21,22), and showed negligible bias from endogenous inhibitors of the enzyme. This finding and the slightly, albeit non-significantly, higher AUC value ( Table 2) mean that uHex is superior to eAAP as a possible clinical marker.…”
Section: Markersupporting
confidence: 94%
“…Factor analysis of the markers studied revealed that the liver and kidney origins of the markers were independent factors, and showed significant correlation within, but not between, the two marker groups. These findings indicate that these marker groups represent metabolically unrelated events, which is in agreement with previous studies (20)(21)(22)(23) and suggests that combining representatives of these marker groups would be of diagnostic advantage. This indication was confirmed by the stepwise discriminant analysis, which showed highest diagnostic potential for the combination of GGT and uHex data into a composite marker and no significant gain from adding any of the remaining markers to this combination.…”
Section: Markersupporting
confidence: 91%
See 2 more Smart Citations
“…The most common traditional marker is gamma-glutamyltransferase (GGT) (287). The liver enzymes aspartate aminotransferase (AST) and alanine aminotransferase (ALT) are also measured as biomarkers of heavy alcohol consumption in routine screening for liver damage (288).…”
Section: Translational Strategies and Need For Continued Biomarkementioning
confidence: 99%